A culinary laboratory for nutrition education. (25th June 2015) - Jacob, Michael; Stewart, Patricia; Medina‐Walpole, Annette; Fong, Chin‐To
Summary: Background: Proficiency in medical nutrition requires an understanding of food‐related biochemistry and the application of this knowledge in the context of culinary, cultural, psychosocial and interprofessional components. Context: Our aim was to develop a teaching format where medical students could learn the biochemistry of nutrition in the context of patient narratives, interactive cooking and dialogues with nutrition professionals. Innovation: We designed and implemented a day‐long culinary laboratory intervention (lab), which is taught to first‐year medical students at the University of Rochester with the help of dietetic interns from Cornell University. Here, we present the details of the intervention, the resources used and the preliminary outcomes on student attitudes. We designed and implemented a day‐long culinary lab, which is taught to first‐year medical students Methods and results: A questionnaire with quantitative rating scales and open‐ended questions was used to probe student attitudes regarding the educational approach used in the lab. Our preliminary findings suggest that the lab was well received and that the dietetic interns were viewed as effective teachers in this context. Implications: A culinary lab is a feasible educational environment for integrating the breadth of topics within the discipline of nutrition. The experiential, food‐based format appears to stimulate questions central to current nutritional controversies, particularly challenges related to translating biochemical mechanism into practical nutrition interventions. Close involvement with basic science faculty members, clinical faculty members and allied health professions are essential for this type of endeavour.